Catechins of GMB-4 Clone Inhibits Adipogenesis Through PPAR-γ and Adiponectin in Primary Culture of Visceral Preadipocyte of Rattus Norvegicus Wistar - Aswaty Nur; Retty Ratnawati; Diana Lyrawati (Research Journal of Life Science, 2018)
Catechins of green tea (Camelia sinensis) GMB4 clone may serve as a potential therapeutic antiobesity agent, probably through its effects on preadipocytes. Thus, to evaluate such antiobesity effects, we performed series of in vitro experiments using primary cultures of visceral preadipocytes from Rattus norvegicus strain Wistar. Quick Cell Proliferation assay, Oil Red-O staining, ELISA and immunocytochemistry were used to determine the effects of 25 µM, 50 µM, 75 µM, and 100 µM catechins on primary culture of preadipocytes, particularly on cell viability and differentiation as well as on expression of relevant obesity genes i. e. PPARγ and adiponectin levels. The results showed that there were no significant differences on preadipocytes viability among control and catechins treatments except in cells treated with 50 µM catechins (means±SD=128±2.47) which resulted 28% higher viability than control (p= 0.037). Catechins inhibited preadipocytes differentiation into adipocytes, at 100 µM up to 78% lower than control. The level of PPARy apparently was reduced by catechins, but statistically significant only at 75 μM (p= 0.029). In contrast, the adiponectin level on preadipocytes increased by catechins at 75 µM and 100 µM (0.786±0.126 and 0.673 ±0.319 ng/ml; control: 0.077±0.017, p ≤0.01). In conclusions, our data revealed that desired antiobesity effects of catechins of green tea GMB4 clone on visceral preadipocytes were concentration-dependent; at dosage 50 µM catechins enhanced cell viability; at more than 75 µM inhibited differentiation of preadipocytes and was associated with lower PPARy and higher adiponectin levels.